Control, Regulations And Legitimacy Of An Islamic Bank: An Indonesian Case Study - Adib, Noval (2014)
This is a research about an Islamic bank in Indonesia that has managed to maintain its existence and grown over the two decades of its operation in Indonesia. The purpose of this research is to understand how the bank gains and maintains its legitimacy from its diverse stakeholders, specifically in terms of the way the bank is regulated/controlled and how the external control mechanism influences the bank’s internal practices of the bank. This research also reviews the history of banking, in general, as well as of Islamic banking in Indonesia to obtain a contextual understanding of the issues This research uses a case study approach informed by the new institutional sociology (NIS) and legitimacy theory. The NIS theory is used to analyse how the Islamic bank responds to pressure and influence from the stakeholders. The legitimacy theory is used to analyse how the Islamic bank gains and maintains its legitimacy from the stakeholders. Data were generated from 24 interviews with the management of the bank and as the regulators as well as from documentary evidence and observations. This research found that the bank faced various pressures and influences with the most critical pressure coming from the regulator through control and regulations. However, the pressures are sometimes conflicting; with investors demanding high profit while the public expect the bank to play a social role. The bank finds innovative ways to respond to such conflicting pressures, and, as a result, gains legitimacy from its stakeholders.